1994
DOI: 10.1111/j.1751-1097.1994.tb05155.x
|View full text |Cite
|
Sign up to set email alerts
|

PRESUMED PHOTORECEPTOR PROTEIN AND ULTRASTRUCI'URE OF THE PHOTORECEPTOR ORGANELLE IN THE CILIATED PROTOZOAN, Blepharisma

Abstract: Abstract‐The red pigment granule of Belpharisma japonicum is believed to be a photoreceptor organelle mediating photodispersal. Freeze‐fracture and thin section electron microscopy revealed that the pigment granules contained a honeycomb‐like structure constructed of folded membranes. In the fracture face of the honeycomb‐like structure, small membrane particles were observed, which might correspond to pigment—protein complexes. The pigment granules were isolated and detergent‐solubilized. Sodium dodecyl sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…As BP molecules in the granule are quite closely packed (29), it is reasonable to conceive that in vivc they can also be tightly associated with possible electron acceptors. In such a case, an efficient photoinduced electron transfer can occur even if the acceptor molecules have more negative reduction potentials.…”
Section: Discussionmentioning
confidence: 99%
“…As BP molecules in the granule are quite closely packed (29), it is reasonable to conceive that in vivc they can also be tightly associated with possible electron acceptors. In such a case, an efficient photoinduced electron transfer can occur even if the acceptor molecules have more negative reduction potentials.…”
Section: Discussionmentioning
confidence: 99%
“…The free‐swimming protozoan, Blepharisma japonicum , has numerous pigment granules containing quinone pigments [1], called blepharismins (Fig. 1 ) [2]; these granules are located just beneath the plasma membrane [3,4]. The pigments are considered to function as photoreceptors modulating the photobehavior of the cell [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The complete molecular structure has been determined in the case of blepharismin (for both red and blue form) (Checcucci et al, 1997;Maeda et al, 1997) and stentorin (Spitzner et al, 1998), while it is still unknown in the case of fabrein (Marangoni et al, 1996). In all cases the photoreceptor pigment was described as confined in pigment granules located below the plasma membrane (Marangoni et al, 1996;Matsuoka et al, 1994;Song, 1981) and it was thought that light stimulation caused a proton release in the cytoplasm, which, in an unknown way, could finally alter the membrane potential and cause modifications of the ciliary beating. Moreover, it was suggested that at least in B. japonicum there could have been a different distribution of the pigments along the cell body .…”
Section: Introductionmentioning
confidence: 98%